Solid acid catalyst derived from spent coffee ground for biodiesel production via esterification of oleic acid and methanol - Law, Zhi Pin (2023)
The transesterification process catalysed by a homogeneous basic catalyst is the most common reaction used for biodiesel production. The major concerns of such catalysts are the difficulties in separating the catalyst after reaction, sensitivity to the free fatty acids and moisture contents in the feedstock. In contrast, a solid acid catalyst can ease the downstream separation and is less likely to be influenced by the free fatty acid in the feedstocks. In this work, biomass waste was used to derive the solid acid catalysts subjected to the transesterification process to lower the cost for biodiesel production. This study aimed to evaluate the possibility of spent coffee grounds being converted into effective carbon precursors and acidic catalysts for biodiesel production. The biomass waste was treated via direct sulfonation with concentrated sulfuric acid at different temperatures ranging from 80 ℃ to 240 ℃. Various catalyst characterisations, including Scanning Electron Microscopy Equipped with Energy Dispersive X-ray, X-ray Diffraction, Fourier Transform Infrared Spectroscopy, surface analysis (BET and BJH methods) and acid density, were carried out to examine the impact of sulfonation temperatures on the catalytic performance. The catalyst with optimum properties was used in the transesterification process at 80 ℃ and rotational speed of 500 rpm for 7 hours to study the effect of catalyst loading and methanol-to-oleic acid molar ratio on biodiesel yield. The catalyst loading was manipulated from 4 to 20 wt.%, whereas the molar ratio was changed from 4:1 to 20:1. It was found that the acid density and catalytic performance improved with increasing sulfonation temperature until the optimum 200 ℃. The catalytic properties of the sample dropped beyond the optimum temperature. Moreover, the optimum catalyst loading and methanol-to-oleic acid were 12 wt.% and 16:1, respectively. The biodiesel yield of 99.67 % was achieved from the transesterification process catalysed by 12 wt.% of the catalyst sulfonated at 200 ℃ and 16:1 of methanolto-oleic acid molar ratio. The results of present work proved the potential of spent coffee grounds to be converted into useful heterogeneous acid catalysts for the transesterification process to produce biodiesel in a relatively environmentally benign way.